Decentralized optimization operation for the multiple integrated energy systems with energy cascade utilization. (15th December 2020) - Mu, Chenlu; Ding, Tao; Qu, Ming; Zhou, Quan; Li, Fangxing; Shahidehpour, Mohammad
Highlights: Optimal dispatch for an integrated energy system with multiple plants is proposed. Energy cascade utilization among multiple plants can reduce operational cost. Alternating direction multiplier method is designed for decentralization to preserve data privacy. Abstract: Integrated energy systems (IESs) integrate and coordinate multiple types of energy resources, which feature enhanced energy efficiency in a wide area. Herein, energy cascading utilization technique is an effective way for multiple IESs to improve the energy utilization efficiency and reduce the operation cost by reutilizing the waste heat in the optimal dispatch model. In this paper, we focus on the small-sized IES which can refer to a plant. Here, an economic dispatch model is set up for multiple IESs to obtain an optimal dispatch decision with energy cascading utilization techniques. Furthermore, in order to preserve the privacy of participating plants, a decentralized optimization framework is proposed to solve the optimal dispatch model using an alternating direction multiplier method (ADMM), where only a limited set of information is shared among participants while convergence is guaranteed. Numerical results verify the effectiveness of the proposed model and its solution method.